The power of unreasonable people how social entrepreneurs create markets that change the world - Elkington, John. (Boston Harvard Business School Press, 2008)
Renowned playwright George Bernard Shaw once said "The reasonable man adapts himself to the world, the unreasonable one persists in trying to adapt the world to himself. Therefore all progress depends on the unreasonable man." By this definition, some of today's entrepreneurs are decidedly unreasonable--and have even been dubbed crazy. Yet as John Elkington and Pamela Hartigan argue in The Power of Unreasonable People, our very future may hinge on their work.
Includes bibliographical references and index.
Keywords: Social entrepreneurship